(untitled) (IAHS Medical Journal, 2022)
Background: Traditionally Gustilo III B fractures are treated with external fixators initially, which leads to various complications. Purpose of this study was to evaluate the role of definitive management of Gustilo type III B tibia fractures with intramedullary nailing and flap coverage within two weeks on overall outcome. Materials and methods: This was a single group clinical trial and was conducted in the Department of Orthopedic Surgery and of Burn and Plastic Surgery of CMCH for a period of two years. Twenty two patients were enrolled through inclusion and exclusion criteria. Patients were followed up for 15 months and overall outcomes were measured by Tucker criteria. Results: In this study, Out of 22 patients, male (90.9%) were more than female (9.1%). According to post-operative complications, superficial infection was in 09 (40.9%) patients, deep infection was in 05 (22.7%) patients, 07 (35%) patients had delayed-union, 05 (25%) patients had non union and only 01 (05%) patient had knee stiffness. Mean ± SD time for fracture union was 11.27 ± 2.738 months (Range: 8-15 months). Functional outcome at the final follow-up, 10 (50%) had excellent outcome. Good outcome was in 02 (10%), fair outcome was in 03 (15%) and poor outcome was in 05 (25%) patients respectively according to Tucker et al. criteria, Post-operative infection and non union showed statistical significance according to p value. Conclusion: After 15 months of surgery, intramedullary nailing and flap coverage within two weeks is a feasible treatment option for Gustilo type III B tibia fractures providing excellent to good outcome, minimum fracture union time and low rate of complications. IAHS Medical Journal Vol 4(2), December 2021; 24-27